Cloning and functional characterization of a retinoid X receptor orthologue in Platynereis dumerilii: An evolutionary and toxicological perspective. (September 2017) - André, Ana; Ruivo, Raquel; Capitão, Ana; Froufe, Elsa; Páscoa, Inês; Costa Castro, Luís Filipe; Santos, Miguel Machado
Abstract: In the present work we provide the first isolation and functional characterization of a RXR orthologue in an annelid species, the Platynereis dumerilii . Using an in vitro luciferase reporter assay we evaluated the annelid receptor ability to respond to ligand 9- cis -retinoic acid, TBT and TPT. Our results show that the annelid RXR responds to 9- cis -retinoic acid and to the organotins by activating reporter gene transcription. The findings suggest a conserved mode of action of the receptor in response to a common signaling molecule and modulation by organotin compounds between vertebrates and Lophotrochozoans. Graphical abstract: Highlights: First time isolation and functional characterization of RXR from Annelids. Annelid RXR conserved transcriptional activation response in the presence of 9-cis-RA. Annelids RXR-signaling pathway is a target of environmental pollutants including organotins.